Epiploic Appendicitis in a pregnant woman. Case presentation - Mayquel Monzón Rodríguez; Yoan Hernández Cabrera; Ailén Sed Pérez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
Acute surgical abdomen during gestation is an entity difficult to manage for both obstetricians and surgeons. Its diagnosis becomes more difficult due to the anatomical and physiological changes modifying the symptoms and signs of some conditions which cause this entity. In these cases, if surgery is not performed in a short time, it produces increasingly serious complications which directly affect maternal and peri-natal morbidity and mortality. For these reasons, a case of a 28.3-week-old pregnant woman, attended at the General University Hospital Dr. Gustavo Aldereguía Lima, in Cienfuegos, was diagnosed an acute surgical abdomen due to epiploic appendicitis based on clinical and humoral elements , aided by multiple diagnostic tools. The management of this case is presented.